Thinking about Persons: Loci Personarum in Humanist Dialectic Between Agricola and Keckermann. Issue 1 (2nd January 2017) - Heßbrüggen-Walter, Stefan
Abstract : Loci personarum, 'topics for persons' were used in Latin rhetoric for the description of persons, their external circumstances, physical attributes, or qualities of character. They stood in the way of fusing rhetoric and dialectic, the goal of sixteenth-century 'humanistic' logic: the project of a unified theory of invention depends on the exclusion of loci personarum from the domain of dialectic proper. But still they cannot easily be replaced in the class room. Bartholomaeus Keckermann resolved these difficulties: he proposed to abandon the notion that loci personarum could play a role in finding new arguments concerning persons. So they pose no risks for a unified theory of invention, because they can only be used for the exposition of information that we already have. Since loci personarum are concerned with individuals, the knowledge about individuals that is available to us is inescapably circumstantial and contingent, defying the claim of generality or necessity of dialectic made by Keckermann's sixteenth-century predecessors. However, our thinking about persons is primarily interested in those aspects that we do not share with other members of our species. For Keckermann, persons are therefore logically different from most individuals belonging to other species.